Peningkatan Problem Solving Skill melalui LKM Berbasis Scaffolding pada Murid Kelas VII SMP Negeri 7 Jember - Ni’matun Nailil Izza; Nery Safitri; Sri Wahyuni; Jiniari Apriska Dewi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to improve the problem solving skills of 7F class students at SMP Negeri 7 Jember in science learning through the implementation of scaffolding-based Student Activity Units (LKM). The problem underlying this study is the low problem solving skills of students in the learning process. This study uses the Classroom Action Research (CAR) method with the Kemmis and MCTaggart models which are carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The study was conducted in the even semester of the 2025/2026 academic year with research subjects consisting of 32 students in 7F class. Research data were obtained through problem solving ability assessment sheets in each cycle. The results of the study showed an increase in problem solving skills through the implementation of scaffolding-based Student Activity Units (LKM). In the first cycle, only 17 of 32 students (53.13%) achieved the KKM with an average of 67.2. After improvements were made in the second cycle, the number of students who completed the learning increased to 29 students (90.63%) with an average of 87.3. Thus, the implementation of scaffolding-based student worksheets (LKM) has been proven to improve the problem-solving skills of 7th-grade students at SMP Negeri 7 Jember.